Control of a Tower Crane with a Pragmatic Hierarchical Algorithm - Abduljabbar, Bilal H.; Billingsley, John (Journal of Applied Nonlinear Dynamics, 2026)
Tower crane systems are commonly used at construction sites. The need to damp the swinging of the load presents a task requiring great skill for manual control. This has led earlier researchers to apply elaborate control strategies. In this paper, we propose the use of a ’pragmatic’ paradigm to define a system that can move the load to the desired target with little or no swing. The essence of pragmatic control is gleaned from autopilot designs of half a century ago. The control is designed as a set of ’nested loops’. The error in an outer loop defines a demand value for the next inner loop, so for example the load position error defines a corrective velocity. In each case the demand is subjected to a limit. This is continued through each layer until the innermost loop, which might take the form of a velocity loop wrapped around a motor to give crisp velocity control. The dynamic model is derived as a state space representation. The proposed strategy was tested by MATLAB which showed that the strategy is successful and effective to control a tower crane system and suppress the load swing. Comparisons are made between the performance of this simples control strategy and that of the complex published alternatives.